ANALISA KEHILANGAN MINYAK (OIL LOSSES) PADA PROSES PRODUKSI DI PABRIK KELAPA SAWIT - SAUKANI, MHD AHYAR; Apriyanti, Siti Nur; Butar-Butar, Revaldo; Manurung, Emy Fadillah; Putra, Pramono Dimas Dwi; Raja, Pada Mulia; Purwanto, Heri; Zakwan; Rahimah (Jurnal Agro Fabrica, 2025)
Oil losses in crude palm oil (CPO) production significantly impact process efficiency and industrial profitability. This study analyzes the causes and extent of oil losses at various processing stages, including empty fruit bunches, pressed fiber, nuts, and liquid effluent, using Soxhlet extraction with n-hexane solvent. Results indicate that while total oil losses remain within acceptable limits, certain components such as empty fruit bunches and liquid effluent exceed standard thresholds. Key contributing factors include raw material quality (underripe or residual fruit), equipment inefficiencies (such as digester maceration and centrifuge separation), and operational errors. The Soxhlet extraction method proved effective in measuring oil losses due to its ability to separate compounds based on density differences without damaging oil components. This study recommends improvements in sterilization processes, equipment optimization, and enhanced operational monitoring to reduce oil losses. The findings provide valuable insights for the industry to enhance production efficiency and minimize economic losses